PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN MEDIA VISUAL INTERAKTIF SERTA MODEL KOOPERATIF STAD - Mega Puspita Sari (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2017)
The purpose of this study is to determine the activities of students, teacher activities and learning outcomes of students of class V semester 2 in learning IPS in SDN Blawirejo Kecamatan Kedungpring Lamongan Year Lesson 2016/2017. In addition, this research is also to know the Application of Interactive Visual Media with STAD Cooperative Model to improve the learning result of IPS Material of Struggle Against Colonial Class V SDN Blawirejo Kecamatan Kedungpring Lamongan District Lesson Year 2016/2017. The result of this research is student activity on cycle I student activity is in enough category with average percentage overall 17,93%. Student activity on the implementation of learning cycle II has increased as much as 11.2%, is in the active category with an overall average percentage of 29.13%. Student learning outcomes in the first cycle average student learning outcomes of 69.5 with the percentage of classical learning completeness 50% with less category, then on the second cycle average student learning outcomes 81.2 with the percentage of learning completeness classical 80% with very category both experienced an increase of 30%. This indicates that this research has succeeded, because the evaluation result has fulfilled the KKM which has been determined.